2011
DOI: 10.1007/s11010-011-0987-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the PPARG P12A and C161T gene variants on serum lipids in coronary heart disease patients with and without Type 2 diabetes

Abstract: We investigated whether PPAR-γ2 gene polymorphisms are associated with serum lipids and the occurrence of coronary heart disease (CHD) prospectively characterised for the presence or absence of Type 2 diabetes in a Turkish population. Our study included 202 patients with CHD (102 with diabetes, 100 without diabetes) and 105 controls. PPARγ genotypes were determined by PCR-RFLP technique. The PPARγ-C161T CC homozygote genotype was associated with significantly increased CHD risk when compared with the T allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 33 publications
1
29
0
2
Order By: Relevance
“…31,32,36,37,41 However, Gu et al 42 and Yilmaz-Aydogan et al 43 reported that the T161 allele carriers had higher serum TG.…”
Section: Ppar Gene Variants and Obesity In Malaysians -Chia Et Almentioning
confidence: 99%
“…31,32,36,37,41 However, Gu et al 42 and Yilmaz-Aydogan et al 43 reported that the T161 allele carriers had higher serum TG.…”
Section: Ppar Gene Variants and Obesity In Malaysians -Chia Et Almentioning
confidence: 99%
“…PPARγ is expressed predominantly in adipose tissue and is a master regulator of lipoprotein metabolism, glucose homeostasis, and vascular homeostasis (Wang, 2010;Yilmaz-Aydogan et al, 2011). The two isoforms of PPAR γ (γ1 and γ2) differ at their N-terminus, and the PPARγ2 isoform is specific to adipose tissue (Shi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other articles were screened out as follows: letters, reviews, and meta-analyses (N = 4), non-human studies (N = 75), articles not related to the research topics (N = 62), not case-control or cohort studies (N = 20), irrelevant to CVD (N = 59), irrelevant to PPARγ2 (N = 37), and not in conformity with Hardy-Weinberg equilibrium (HWE) (N = 1). In the end, a total of 12 relevant case-control studies, published between 2004 and 2013, were included in this metaanalysis, involving 10,189 patients with CVD and 17,899 controls (Tobin et al, 2004;Nassar et al, 2006;Zee et al, 2006;Rhee et al, 2007;Ruiz-Narváez et al, 2007;Dallongeville et al, 2009;Vogel et al, 2009;AshokKumar et al, 2010;Galgani et al, 2010;Yilmaz-Aydogan et al, 2011;Ho et al, 2012;Youssef et al, 2013). The sample sizes ranged from 300-9758 and included 1070 patients with MI, 7849 with CAD, and 1270 with acute coronary syndromes (ACS).…”
Section: Overview Of the Study Characteristicsmentioning
confidence: 99%
“…14 PPAR'ların aterosklerotik lezyonların gelişiminde önemli etki gösterdikleri bilinmektedir. 10,[15][16][17] Aterosklerozda damar cidarında gelişen köpük hücrelerinde PPAR gama (PPARG) anlatı-mının yüksek olması aterosklerotik lezyonları şid-detlendirdiğinin işareti olarak önerilmiştir. 18,19 PPARG adiposit farklılaşması, lipid metabolizması ve glukoz homeostazının yer aldığı yolaklarda çok sayıda hedef genin ekspresyonlarının düzenlenme-sine katılmaktadır.…”
unclassified
“…16,19 Daha önce yine Türk toplumunda gerçekleştirdiğimiz çalışmada ise, PPARG C161T CC genotipi artmış KKH riski ve yüksek serum TAG düzeyleri ile ilişkili bulunmuştur. 17 Metabolik hastalıklarda ve sağlıklı koşullarda PPARG gen varyasyonlarının serum lipid düzeylerine etkisi yoğun olarak araştırılmasına karşın, lipoprotein alt fraksiyon düzeyleri ile ilişkisi sadece bir çalışmada incelenmiştir. Japon populasyonunda PPARG P12A varyasyonunun sdLDL düzeylerindeki artışın genetik alt yapısını oluşturduğu önerilmiştir.…”
unclassified